Synthesis, Characterization and Elucidation of the Structure–Activity Relationship of Heteroatom Donor Ligands and Their Complexes Derived From Substituted Dithiocarbazate Derivatives - How, Fiona Ni Foong (2008)
Four new substituted dithiocarbazate ligands [S-napthalen-2-ylmethyldithiocarbazate (SNMDTC), S-quinolin-2-ylmethyl-dithiocarbazate (SQ2MDTC), Sbenzyl- N-benzyldithiocarbazate (SBNBDTC) and S-methyl-N-benzyldithiocarbazate (SMNBDTC)], eight series of isomeric Schiff bases derived from different types of S-substituted dithiocarbazate and their metal complexes were successfully synthesized and characterized. Eighteen structures were determined using single crystal X-ray diffraction analysis. These newly synthesized compounds were systematically designed to form structurally heterogeneous compounds for QSAR study. Schiff bases were derived from condensation of isomeric aldehydes and ketones, 3- and 4-methylacetophenone and 2-, 3- and 4-acetylpyridine with different substituted dithiocarbazate compounds. Upon complexation, all Schiff bases formed bis chelated (NS donor) complexes except for the uninegative tridentate, S-napthalen- 2yl methyl-β-N-(2-acetylpyridine)dithiocarbazate (SNM2AP) that coordinated with metal ions via the azomethine nitrogen atom, the pyridyl nitrogen atom and the thiolo sulfur (NNS donor) Some of these newly synthesized compounds exhibited significant activities towards selective strains of pathogens and marked cytotoxicity when assayed against breast cancer estrogen receptor positive, MCF-7 and breast cancer estrogen receptor negative, MDA-MB-231 cell lines. The biological activities of the isomeric Schiff bases and their complexes were investigated. Most of the complexes exhibited higher activity compared to their parent ligands upon complexation with metal ions. The cytotoxicity data for all the compounds were used to construct QSAR model in an attempt to elucidate the relationship between structure and bioactivity. Satisfactory QSAR models were developed focusing on a few of the informative descriptors based on a wide set of relatively heterogeneous compounds as evidenced with value r2>0.6 and r2 CV> 0.5.